Designing drugs by molecular docking to inhibit COVID-19 - Kareem , Abbas; A. Saeed, Bahjat ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The current coronavirus (COVID-19) pandemic has raised the profile of the new generation SARS-CoV-2 virus as a global health threat and its massive spread to every corner of the world has raised major concerns about the public healthcare system due to the lack of effective and reliable treatments. Therefore, it is necessary to use all possible methods to design new drugs and vaccines to reduce the disease. In this study, we designed eight Emmdpd ,Favlplravir, Hydroxychloroquine and Kifunensine -derived molecules and examined their biological potential to inhibit the main protease (Mpro) of SARS-CoV-2 through computational studies, Density Function Theory (DFT) calculations were performed on the studied compounds. Which improved the geometric structure of the compounds, The geometrically optimized structures were subjected to molecular docking calculations using the SARS-CoV-2 major protease Protein Database ID 6LU7 , Compounds 4h, 6b, 9f and 14h showed favorable pharmacological properties suitable for human use. DOI: https://doi.org/10.54633/2333-025-058-002